A Meta-Analysis on the Risk Factors of Low Back Pain in Health Workers - Muh. Syaiful Akbar; Setyo Sri Rahardjo; Dono Indarto (Journal of Epidemiology and Public Health, 2020)
Background: Low back pain is a common prob